2012
DOI: 10.1620/tjem.228.109
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Osmolar Gap Is Predictive of Contrast-Induced Acute Kidney Injury

Abstract: Contrast-induced acute kidney injury (CIAKI) is a common complication after percutaneous coronary artery intervention (PCI). It is urgent to find a novel, easily measurable and accurate predictor for the early detection of CIAKI. Hyperosmolarity and large amounts of contrast media are risk factors for CIAKI. However, there is no study on plasma osmolar gap as a predictor of CIAKI. We enrolled 89 patients undergoing elective PCI and tested changes of serum sodium, osmolar gap, and renal function at 0, 6, 12 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Recently, Kim et al determined a relationship between CIN and osmolar gap. 2 The findings of these 2 studies support each other. However, we have some concerns about the methodology used in the Yildiz et al's study.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Recently, Kim et al determined a relationship between CIN and osmolar gap. 2 The findings of these 2 studies support each other. However, we have some concerns about the methodology used in the Yildiz et al's study.…”
supporting
confidence: 55%
“…The osmolar gap is obtained by subtracting the osmolarity value calculated from the osmolality measured by an osmometer. 2 Increased ethanol, methanol, and some molecules in plasma may cause an elevated osmolar gap. 3 Osmolarity calculated by the formula often does not provide a directly measured osmolarity value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, many previous studies had limited the diagnosis time frame of CI-AKI to 48 hours, or even 24 hours [9,25]. In the study conducted by Kim et al, CI-AKI was defined as an increase in SCr of ≥50% or 0.3 mg/dL, or a decrease in eGFR of ≥25% within 24 hours after PCI [25]. e present simple nomogram was constructed based on age, AMI, IABP, and CKD, which are common risk factors associated with CI-AKI, as reported by numerous previous studies [12,26,27] 3) were identified as independent risk factors for CI-AKI [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we noticed that some patients were missing SCr data on day 3, which may lead to the underestimation of the incidence of CI-AKI. However, many previous studies had limited the diagnosis time frame of CI-AKI to 48 hours, or even 24 hours [9,25]. In the study conducted by Kim et al, CI-AKI was defined as an increase in SCr of ≥50% or 0.3 mg/dL, or a decrease in eGFR of ≥25% within 24 hours after PCI [25].…”
Section: Discussionmentioning
confidence: 99%